Nucleolar Division in the Promastigote Stage of Leishmania major Parasite: A Nop56 Point of View. (10th October 2018) - Nepomuceno-Mejía, Tomás; Florencio-Martínez, Luis Enrique; Martínez-Calvillo, Santiago
Abstract : Nucleogenesis is the cellular event responsible for the formation of the new nucleoli at the end of mitosis. This process depends on the synthesis and processing of ribosomal RNA (rRNA) and, in some eukaryotes, the transfer of nucleolar material contained in prenucleolar bodies (PNBs) to active transcription sites. The lack of a comprehensive description of the nucleolus throughout the cell cycle of the human pathogen Leishmania major prompted us to analyze the distribution of nucleolar protein 56 (Nop56) during interphase and mitosis in the promastigote stage of the parasite. By in silico analysis we show that the orthologue of Nop56 in L. major (LmNop56) contains the three characteristic Nop56 domains and that its predicted three-dimensional structure is also conserved. Fluorescence microscopy observations indicate that the nucleolar localization of LmNop56 is similar, but not identical, to that of the nucleolar protein Elp3b. Notably, unlike other nucleolar proteins, LmNop56 remains associated with the nucleolus in nonproliferative cells. Moreover, epifluorescent images indicate the preservation of the nucleolar structure throughout the closed nuclear division. Experiments performed with the related parasite Trypanosoma brucei show that nucleolar division is carried out by an analogous mechanism.